Imaging Modern Decay: The Aesthetics of Ruin Photography - Pétursdóttir, Þóra; Olsen, Bjørnar (Journal of Contemporary Archaeology, 2014)
Photographs of abandoned homes, decaying towns and industrial ruins swarm the Internet. They also fill the glossy pages of art books and popular magazine issues, and are increasingly appropriating more prominent spaces in scholarly publication on modern decay and abandonment. While its popularity speaks to its attractiveness, this proliferating ruin imagery has also become the target of harsh criticism from both concerned scholars and people affected by ruination. To them much of this is little but “ruin porn”: a superficial and one-eyed portrayal of urban decay that turns social and material misery into something seductive and aesthetically pleasing. This paper takes a different position. Speaking from an archaeological perspective, and especially the archaeology of the contemporary past, it argues that the new engagement with ruin photography rather calls for a reconsideration and appreciation of the role of photography; not merely as a means of documentation but also an interactive and attentive way to approach things themselves. By scrutinizing what the critics have claimed to be the fallacies of the image (its selectivity, timelessness, superficiality and tendency to aestheticize), and by emphasizing ruin photography as an engagement with things, the paper aims to show that it is precisely the alleged shortcomings that make photography a valuable method in a new approach to things and ruins.